Pattern Anlysis of Risk-Reducing Strategies in Unaffected Korean BRCA1/2 Mutation Carriers - Dabin Kim; Jai Min Ryu; Sang-Ah Han; Zisun Kim; Sung-Won Kim (Current Oncology)
The lifetime risk of breast and ovarian cancer increases substantially for individuals with mutations in BRCA1/2. The evidence indicates that BRCA1/2 mutation carriers benefit from early cancer detection and prevention strategies. However, data on the patterns of risk-reducing interventions are lacking. This study investigated the patterns of surveillance and risk-reducing interventions among unaffected BRCA1/2 mutation carriers. A cohort of unaffected BRCA1/2 mutation carriers was identified from the Korean Hereditary Breast cAncer (KOHBRA) study database, and a telephone survey was conducted. The survey included questions on the incidence of new cancers, patterns of cancer (breast, ovarian, prostate, other) surveillance, chemoprevention, risk-reducing surgery, and reasons for participating in risk-reducing strategies. Between November 2016 and November 2020, 192 BRCA1/2 mutation carriers were contacted, of which 83 responded. After excluding 37 responders who refused to participate, 46 participants (15 males, 31 females) were included in the analysis. The mean ± SD follow-up time was 103 ± 17 months (median 107, range 68~154), and the mean ± SD age was 31 ± 8 years. Ten BRCA1/2 mutation carriers developed breast cancer, one developed ovarian cancer, and three developed other cancers. Six BRCA1/2 mutation carriers (19.4%) underwent annual breast cancer surveillance as recommended by guidelines, while none underwent ovarian or prostate cancer surveillance. Three carriers (9.7%) used chemoprevention for breast cancer. Risk-reducing salpingo-oophorectomy was performed on only one BRCA1/2 mutation carrier. The rates of breast/ovarian cancer surveillance, chemoprevention, and risk-reducing surgery were low among unaffected Korean BRCA1/2 mutation carriers. Given this cohort’s relatively high risk of developing breast cancer, strategies to encourage active participation in risk reduction are needed.